A Scoping Review on Technical and Vocational Education and Training (TVET) Practices for Environmental Sustainability in Zimbabwe - Mutuke, Mathias; Katsande, Daphne Idith; Sirimoyi, Fortune Kudzai (European Journal of Applied Sciences, 2025)
This study aimed to conduct a scoping review of environmental sustainability practices in TVET institutions in Zimbabwe. The study’s objectives were to identify interventions within Zimbabwe’s TVET sector that promote environmental sustainability, to examine the various challenges being faced in the implementation of environmental sustainability approaches in TVET institutions in Zimbabwe and to proffer strategies to foster the implementation of sustainability approaches in TVET institutions in Zimbabwe. The PRISMA-ScR methodology was used to review both scholarly and gray literature from 2020 to 2025. The study’s scope was based on green campus, green curriculum, green community, green research, and green culture. A sample of 47 documents were used in this scoping review. The scoping review’s findings indicated that there were notable green initiatives that were being implemented by TVET institutions in Zimbabwe such as the installation of clean energy, green curriculum (although the adoption is uneven between private and public institutions), and community engagement programmes. However, some challenges are being faced such as financial constraints, bureaucratic delays to adopt a new curriculum that includes sustainability aspects, and incapacitated lecturers. Recommendations such as prioritizing investments in green infrastructure, shift in procurement policies, integration of sustainability concepts in the curriculum and provision of ongoing training for the lecturers were made.